2015
DOI: 10.1038/cmi.2015.71
|View full text |Cite
|
Sign up to set email alerts
|

CD4+VEGFR1HIGH T cell as a novel Treg subset regulates inflammatory bowel disease in lymphopenic mice

Abstract: Regulatory T cells (Tregs) are a specialized subpopulation of T cells that control the immune response and thereby maintain immune system homeostasis and tolerance to self-antigens. Many subsets of CD4 1 Tregs have been identified, including Foxp3 1 , Tr1, Th3, and Foxp3neg iT(R)35 cells. In this study, we identified a new subset of CD4 1 VEGFR1 high Tregs that have immunosuppressive capacity. CD4 1 VEGFR1high T cells, which constitute approximately 1.0% of CD4 1 T cells, are hyporesponsive to T-cell antigen r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
(70 reference statements)
2
4
0
Order By: Relevance
“…Further, CD4 + VEGFR1 high T cells are able to suppress the proliferation of CD4 + CD25 neg T cell as efficiently as CD4 + CD25 high natural Tregs in a contact-independent manner by soluble factor-mediated induction of apoptosis, in a model of lymphopenic mice. These findings strengthen the importance of the role of CD4 + VEGFR1 high T cells in the maintenance of immune homeostasis and are additional evidence for the link between the effects of VEGFR1 mediated signaling and the inadequate immune response in tumors [200] (Figure 2).…”
Section: Multifaceted Role Plgf/vegfr-1/nrp1/nrp2 Signaling In Antsupporting
confidence: 68%
“…Further, CD4 + VEGFR1 high T cells are able to suppress the proliferation of CD4 + CD25 neg T cell as efficiently as CD4 + CD25 high natural Tregs in a contact-independent manner by soluble factor-mediated induction of apoptosis, in a model of lymphopenic mice. These findings strengthen the importance of the role of CD4 + VEGFR1 high T cells in the maintenance of immune homeostasis and are additional evidence for the link between the effects of VEGFR1 mediated signaling and the inadequate immune response in tumors [200] (Figure 2).…”
Section: Multifaceted Role Plgf/vegfr-1/nrp1/nrp2 Signaling In Antsupporting
confidence: 68%
“…demonstrated in mouse model that engagement of T‐cell VEGFR‐1 with its ligand (VEGF) induced IL‐10 in isolated spleen T cells and CD4 + T cell clone. 29 Our data are in agreement with these results and demonstrate that VEGFR‐1 signaling enhances IL‐10 production in human T lymphocytes including both CD4 + and CD8 + subsets. Notably, VEGFR‐1 binding with VEGF in Shin's study did not inhibit T cell proliferation.…”
Section: Discussionsupporting
confidence: 91%
“…using goat anti‐mouse VEGFR‐1 polyclonal Abs reported that activated T cells transcribed mRNA of VEGFR‐1 and VEGFR‐2, but expressed only VEGFR‐1 28 . Later these authors reconfirmed the expression of VEGFR‐1 utilizing mAbs and identified a novel subset of regulatory CD4 + T cells with high expression of VEGFR‐1 in peripheral blood 29 . Voron et al.…”
Section: Discussionmentioning
confidence: 99%
“…Tonsillectomy involves the depletion of Treg cells in tonsils and alters the intestinal immune environment through its mucosa‐associated lymphoid system 59 . Tonsillectomy was a CD risk factor in Western and Eastern populations.…”
Section: Discussionmentioning
confidence: 99%